All‐Recyclable Triboelectric Nanogenerator for Sustainable Ocean Monitoring Systems. Issue 30 (9th June 2022) - Ahn, Junseong; Kim, Ji‐Seok; Jeong, Yoonsang; Hwang, Soonhyoung; Yoo, Hyunjoon; Jeong, Yongrok; Gu, Jimin; Mahato, Manmatha; Ko, Jiwoo; Jeon, Sohee; Ha, Ji‐Hwan; Seo, Hee‐Seon; et al.
Abstract: The growing severity of environmental problems such as plastic waste and climate change has inspired active research into solutions based on recyclable and renewable energy devices. Triboelectric nanogenerators (TENGs) that convert wasted mechanical energy into electrical energy offer a solution that needs to be made recyclable to reduce or eliminate the generation of electronic waste (e‐waste) on their disposal. In this study, an all‐recyclable TENG (AR‐TENG) based on a thermoplastic polymer with a nanohole pattern is developed; it delivers an excellent output power density of 1.547 W m −2 (peak output voltage = 360 V, current = 22 µ A) and shows superior mechanochemical stability by maintaining its performance after immersion into seawater or 1 000 000 cyclic tests. The practical utility of this AR‐TENG is demonstrated through its use to power a buoy‐type ocean monitoring system and an intelligent life jacket, whereas recyclability is demonstrated by the re‐fabrication of the AR‐TENG; reusability in other devices is validated by the successful fabrication of a plasmonic color filter. This work paves the way for the efficient harvesting of renewable energy without the concomitant production of e‐waste; therefore, it contributes to the mitigation of global environmental problems such as global warming and ozone depletion. Abstract : An all‐recyclable triboelectric nanogenerator (AR‐TENG) that exhibits high power density and excellent mechanochemical stability is developed. The recyclability is demonstrated through its disassembly and fabrication of the plasmonic color filter. An ocean energy harvesting system based on AR‐TENG is developed and used to power a buoy‐type ocean monitoring system and intelligent life jacket.